Chapter 16: Adaptive and Evidence-based Policymaking: Adaptive and evidence based policies (Rethinking Food Security Policy in Developing Economies, 2026)
The escalating complexities of global agrifood systems, exacerbated by climate change, demographic shifts, and geopolitical instability, demand a critical departure from static, reactive public policy paradigms. This chapter explores the imperative transition toward adaptive and evidence-based policymaking in developing economies, advocating for robust data driven governance, systematic policy experimentation, and the institutionalization of deep feedback loops. By synthesizing empirical research, theoretical models, and diverse regional case studies, the analysis elucidates how continuous learning mechanisms enhance policy durability amidst sociopolitical and environmental volatility. The chapter critically reviews foundational frameworks, specifically the International Food Policy Research Institute’s (IFPRI) Kaleidoscope Model of policy change and Swanson and Bhadwal’s principles for adaptive policymaking. Methodologically, it evaluates the integration of Randomized Controlled Trials (RCTs) and digital public infrastructures in shaping and scaling agricultural interventions. Through detailed empirical analyses including the Kissan Card Subsidy Program in Pakistan’s Punjab province, the institutionalization and subsequent dismantling of the National Council for Food and Nutritional Security (CONSEA) in Brazil, the political economy of policy experimentation in China, and the data-driven initiatives of Ethiopia’s Agricultural Transformation Agency (ATA) the chapter identifies the precise mechanisms that enable successful policy scaling, resilience, and double loop learning. Ultimately, the findings emphasize that autonomous learning institutions, broad stakeholder consensus, and transparent science-policy interfaces are indispensable for developing durable, equitable, and sustainable food security frameworks in the Anthropocene.